FEATURES OF THE COURSE OF CHRONIC GASTRODUODENAL PATHOLOGIES IN CHILDREN ON THE BACKGROUND OF ATOPIC DERMATITIS ACCORDING TO THE DATA OF THE ZERAFSHAN VALLEY - Tursunova Barno Abrorovna,; Tursunkulova Dilshoda Akmalovna,; Makhmudova Sevara Utkir kizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: diseases of the digestive system in children, due to their wide prevalence, clinical course, high risk of early manifestation and disability, represent a serious medical and social problem. In this paper, we studied the features of the course of gastroduodenal pathologies in children against the background of atopy in order to optimize methods of prevention and treatment.